Achieving negative resection margins in oral cavity cancer with masticator space involvement—Is it feasible? International collaborative study. Issue 2 (29th November 2021) - Horowitz, Gilad; De Almeida, John R.; Berania, Ilyes; Goldstein, David P.; Köhler, Hugo Fontan; Kowalski, Luiz Paulo; Matos, Leandro Luongo; Brenner‐Ullman, Adi; Fliss, Dan M.; Muhanna, Nidal; Halpern, Daniel; Nard‐Carmel, Narin; et al.
Abstract: Background: Masticator space involvement in oral cavity squamous cell carcinoma (OCSCC) is considered an unresectable disease. Nevertheless, achieving negative resection margins is feasible in limited masticatory space involvement. Materials and Methods: A multi‐institutional study on OCSCC patients with masticator space invasion who underwent surgical resection. Margin status was assessed according to anatomic tumor involvement of the inframandibular and supra‐mandibular notch. Results: One‐hundred and thirty‐two patients met the inclusion criteria. Then, 67 patients (50.8%) were diagnosed with a supra‐notch tumor and 65 (49.2%) with an infra‐notch disease. Negative margins were more common in the infra‐notch group (43.3 vs. 23.1%, p = 0.014), and positive margins were more common in the supra‐notch group (41.5 vs. 23.9%, p = 0.041). Multivariable analysis demonstrated that supra‐notch tumors had an increased likelihood for involved resection margins (odds ratio = 2.46, p = 0.036). Conclusion: OCSCC patients with masticator space involvement are prone for positive surgical margins in tumors extending above the supra‐mandibular notch.